Studi Komparasi Perilaku Struktur Gedung At-Tauhid Di Kota Surabaya Dengan Menggunakan SNI 1726-2012 Dan SNI 1726-2019 - Heri Istiono; Yasmin Lisawiyani (Jurusan Teknik Sipil, Fakultas Teknik, Universitas Borneo Tarakan, 2022)
The seismic structure based on SNI 1726-2012 has been renewed in SNI 1726-2019 in term of the newest seismic map. This sort of renewal plan is necessary to anticipate the ruin of structure at At-Tauhid building in Surabaya. The plan for reinforced concrete structure was carried out based on SNI 2847-2013. To analyze the quake against the building, the researcher employed structural modeling by SAP 2000 program and eventually yielded the comparisons of spectrum response and structural behavior.The research results demonstrated that the spectrum response of seismic design improved by Sa12.99% and T 7.78%. In terms of control behavior analysis using SNI 1726-2012 and SNI 1726-2019, the structure of building has met the requirements of time period, mass participation, static and dynamic base shears, interstorey drift, and dual systems. Time period obtained the similar value as Ta SAP by 1.61 second. Meanwhile, the mass participation employing SNI 1726-2019 reached faster diverse number at the 30th mode. Static base shear increased 12.99%, whereas dynamic base shear inclined 32.95%. Interstorey drift improved 34.73% in X direction and 34.54% in Y direction. The dual systems based on SNI 1726-2012 got OMRF retaining the seismic force of design 50.83% in X direction and 43.75% in Y direction, whereas SNI 1726-2019 had OMRF resisting the seismic force of design 50.87% in X direction and 43.77% in Y direction.